Fluorescence microscopic visualization of non cellular components during initial bioadhesion in situ - Kensche, A.; Basche, S.; Bowen, W.H.; Hannig, M.; Hannig, C. (Archives of oral biology, 2013)
The formation of an intraoral biofilm is primarily determined by initial bioadhesion processes, including molecular interactions. Therefore, this study aimed to establish fluorescent labelling protocols to enable the simultaneous visualization of different pellicle enzymes, extracellular glucans and adherent bacteria throughout the initial phase of biofilm formation. In situ formed biofilm samples were collected on enamel and dentine slabs that were fixed on buccal sites of individual splints, being worn by 5 subjects. After an intraoral slab exposure from 30min to 8h, the following specially adapted fluorescent labelling assays were performed and analyzed by epifluorescent microscopy: pellicle-amylase, -lysozyme, -peroxidase and -glycosyltransferases B, C and D were marked with specific primary antibodies and then visualized by the aid of different fluorescently labelled secondary antibodies (Texas Red, DyLight 488, FITC). Afterwards the same samples were subjected to a combined DAPI-/Concanavalin A-staining to determine adherent bacteria and glucans. All fluorescence labelling assays were successfully established to visualize pellicle enzymes, glucans and adherent bacteria at different times of biofilm formation. The combination of the labelling protocols showed a characteristic agglomeration of glucans and bacteria as well as an increased concentration of the pellicle enzymes in the initial phase of bioadhesion. Fluorescent labelling techniques are a valuable supplement of dental research as they provide an insight into the mutual interactions of different biofilm determinants in situ. Based hereon, information could also be deduced about the influence of oral therapeutics on individual caries susceptibility.